2002
DOI: 10.1046/j.1460-9568.2002.02305.x
|View full text |Cite
|
Sign up to set email alerts
|

The murine neurokinin NK1 receptor gene contributes to the adult hypoxic facilitation of ventilation

Abstract: Substance P and neurokinin-1 receptors (NK1) modulate the respiratory activity and are expressed early during development. We tested the hypothesis that NK1 receptors are involved in prenatal development of the respiratory network by comparing the resting respiratory activity and the respiratory response to hypoxia of control mice and mutant mice lacking the NK1 receptor (NK1-/-). In vitro and in vivo experiments were conducted on neonatal, young and adult mice from wild-type and NK1-/- strains. In the wild st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 48 publications
4
32
0
1
Order By: Relevance
“…We have also shown that it stains identical structures to those detected by a rabbit antibody (Polgár et al, 1999b), which gives no immunostaining in central nervous system (CNS) tissue from NK1r −/− mice (Ptak et al, 2002). …”
Section: Methodsmentioning
confidence: 77%
“…We have also shown that it stains identical structures to those detected by a rabbit antibody (Polgár et al, 1999b), which gives no immunostaining in central nervous system (CNS) tissue from NK1r −/− mice (Ptak et al, 2002). …”
Section: Methodsmentioning
confidence: 77%
“…In Western blots from rat brain, it recognizes a single band at 46 kDa, whose staining is specifically inhibited by incubation with the blocking peptide (data supplied by the manufacturer). Furthermore, it was shown that it does not produce any staining in NK-1r knockout mice, although it recognizes the receptor in wild-type mice (Ptak et al, 2002).…”
Section: Antibody Specificitymentioning
confidence: 99%
“…The role of SP and NK1-R has been the focus of much research as it is involved in mediating a number of respiratory reflex responses, including hypoxic ventilatory response and central chemosensitivity (Chen et al 1990a;Gray et al 2001;Mazzone et al 1997;Nattie and Li 2002;Ptak et al 2002;Wickstrom et al 2004). Although NK1-R are localized throughout the VRG (Gray et al 1999;Guyenet et al 2002;Nakaya et al 1994;Wang et al 2001) with expression confirmed on preinspiratory neurons , the effect of direct activation of NK1-R expressing expiratory neurons on respiratory rhythm has not been thoroughly explored.…”
Section: Substance P Modulates the Excitability Of Expiratory Neuronsmentioning
confidence: 99%